A Framework for Identifying Causal Factors of Delay in Nuclear Power Plant Projects. (2016) - Alsharif, Samer; Karatas, Aslihan
Abstract: Nuclear power plant projects have unique characteristics (e.g., variability of projects portfolio, processes and procedures, security and safety requirements) that affect precise estimation of project schedule and cost. Inaccurate estimation may result in delay and cost overrun, and accordingly jeopardizing the nuclear power plant's operating license. To reliably estimate projects schedule and cost, the causal factors of delay in nuclear power plant projects need to be carefully investigated and analyzed. This study presents a framework for identifying causal factors of delay for operable nuclear power plants projects. This framework is designed in three main stages: (1) collecting data on projects that experienced delay for various reasons (e.g., missing schedule updates, design errors, scope change); (2) identifying the reasons for delay into standard common causal factors; and (3) analyzing the identified causal factors of delay and their impact on projects schedule and cost performance. This framework will assist decision-makers (e.g., nuclear project managers and project controllers) in identifying and evaluating the nuclear projects causal factors of delay to improve the reliability of projects schedule and cost estimation.